Detection of vaccine-derived poliovirus circulation by environmental surveillance in the absence of clinical cases - John Kofi Odoom; Evangeline Obodai; Gifty Boateng; Stanley Diamenu; Keren Attiku; Patrick Avevor; Ewurabena Duker; Bismarck Boahene; Miriam Eshun; Emmanuel Gberbie; Joseph Kwadwo Larbi Opare (Human Vaccines & Immunotherapeutics, 2021)
Background On August 25, 2019, the Noguchi Memorial Institute for Medical Research notified the confirmation of a circulating-vaccine-derived poliovirus type-2 (cVDPV2) from the Agbogbloshie environmental surveillance (AES) site, in the Greater Accra Region. A field investigation of the outbreak was conducted to describe the results of epidemiological and laboratory investigations, and control efforts. Methods We conducted a descriptive investigation, records review, and active-case-search. Caregivers were interviewed on the vaccination status of their children; knowledge, attitude, and practices on polio prevention; water, sanitation and hygiene practices, and health-seeking behaviors. Stool from healthy children <5 y and sewage samples were taken for laboratory diagnosis. Results cVDPV2 genetically similar to the cVDPV2 diagnosed recently in the Northern Region of Ghana and Nigeria was identified. 2019 half-year coverage of OPV and IPV was 22%. Fully immunized children were 49% (29/59). Most health workers (70%) had a fair knowledge of polio and acute flaccid paralysis (AFP). Forty-six percent of care-givers admitted to using the large drain linked to the site where the cVDPV2 was isolated as their place of convenience and disposing of the fecal matter of their children. No AFP case was identified. Stool samples from 40 healthy children yielded non-polio enteroviruses while 75% (3/4) of the additional sewage samples yielded cVDPV2. Conclusion cVDPV2 was isolated from the AES site. No AFP or poliovirus was identified from healthy children. There is a need to improve health workers’ knowledge on AFP and to address the dire sanitation conditions in the Agbogbloshie market and its environs.